SEM and AES Analysis of Corrosion in Steel Cans of Meat and Poultry Food Industry Influenced by Microorganisms Affecting the Competitiveness in Northwest of Mexico - César Sánchez Ocampo; Gustavo López Badilla; Elizabeth Romero Samaniego; Sandra Luz Toledo Perea; Josefina Campos García (Journal of Spectroscopy)
The food industry of meat and poultry food is very important activity in the economy of the northwest of Mexico where the Sonora state (with Hermosillo and Santa Ana cities as arid and semiarid zones and Guaymas as marine regions) and Baja California state (Mexicali as arid zone and Tijuana as marine region) are located. The meat and poultry industries produce meat, milk, and eggs, which are recommended for their nutritive properties. An evaluation of micro- and nanocorrosion was made with an optical sensor used to detect microorganisms (MO) inside of the steel cans. The techniques applied to evaluate the deterioration were the Scanning Electron Microscopy (SEM) and the Auger Electron Spectroscopy (AES), to obtain the morphology of microorganisms formed in the internal area of the metallic containers. Also the chemical composition to identify and determine the conditions for growth of microorganisms was obtained with respect to moisture and temperature in each region analyzed. The sulfur was the principal pollutant agent in arid and semiarid zones and chloride in marine zones that promoted the corrosion process. The presence of corrosion in the food industry decreases their competitiveness.